Laser Lesion in the Mouse Visual Cortex Induces a Stem Cell Niche-Like Extracellular Matrix, Produced by Immature Astrocytes - Roll, Lars; Eysel, Ulf T.; Faissner, Andreas (Frontiers in Cellular Neuroscience, 2020)
The mammalian central nervous system (CNS) is characterized by a severely limited regeneration capacity. Comparison with lower species like amphibians, which are able to restore even complex tissues after damage, indicates the presence of an inhibitory environment that restricts the cellular response in mammals. In this context, signals provided by the extracellular matrix (ECM) are important regulators of events like cell survival, proliferation, migration, differentiation or neurite outgrowth. Therefore, knowledge of the post-lesional ECM and of cells that produce these factors might support development of new treatment strategies for patients suffering from traumatic brain injury and other types of CNS damage. In the present study, we analyzed the surround of focal infrared laser lesions of the adult mouse visual cortex. This lesion paradigm avoids direct contact with the brain, as the laser beam passes the intact bone. Cell type-specific markers revealed a distinct spatial distribution of different astroglial subtypes in the penumbra after injury. Glial fibrillary acidic protein (GFAP) as marker for reactive astrocytes was found broadly up-regulated, whereas the more immature markers vimentin and nestin were only expressed by a subset of cells. Dividing astrocytes could be identified via the proliferation marker Ki-67. Different ECM molecules, among others the neural stem cell-associated glycoprotein tenascin-C and the DSD-1 chondroitin sulfate epitope, were found on astrocytes in the penumbra. Wisteria floribunda agglutinin (WFA) and aggrecan as markers for perineuronal nets, a specialized ECM limiting synaptic plasticity, appeared normal in the vicinity of the necrotic lesion core. In sum, expression of progenitor markers by astrocyte subpopulations and the identification of proliferating astrocytes in combination with an ECM that contains components typically associated with neural stem/progenitor cells suggest that an immature cell fate is facilitated as response to the injury.